"A lot of them write how they speak": policy, pedagogy and the policing of 'nonstandard' English. (9th August 2022) - Snell, Julia; Cushing, Ian
Abstract: International studies of talk‐intensive (or 'dialogic') pedagogies have demonstrated that children who experience academically challenging classroom discussion ('dialogue') make greater progress than their peers who have not had this experience. In England, gains in achievement have been greatest for pupils from less privileged socio‐economic backgrounds, thus underlining the importance of dialogue to social mobility. However, policy prescriptions on 'standard English' run counter to the principles of dialogic teaching by privileging 'correct' forms of expression over emerging ideas. In this article, we argue that schools can be coerced by macro‐level policy into creating meso‐level policies which police nonstandardised forms in the classroom with the assumption that this will improve literacy rates. We draw upon a corpus of Ofsted reports as well as data collected in primary schools – pupil writing and focus groups, video‐recorded literacy lessons and teacher interviews – to demonstrate that features of spoken dialect grammar occur infrequently in pupil writing, yet the narrative that spoken dialect is a 'problem' within education is driving policy/practice that is detrimental to classroom talk and pupil learning. We argue that this must be addressed urgently if we are to exploit the full potential of talk for learning and for addressing educational inequities.